2007
DOI: 10.1111/j.1447-0756.2007.00686.x
|View full text |Cite
|
Sign up to set email alerts
|

Ureteral catheter placement for prevention of ureteral injury during laparoscopic hysterectomy

Abstract: UC placement is simple, helping to prevent ureteral injury during laparoscopic hysterectomy and enhancing safety of this procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
52
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 31 publications
3
52
0
2
Order By: Relevance
“…In open surgery, as the difficulties of operations increase, the probability of ureteral injury increases by 0-2.0% (Uccella et al, 2007;Chong et al, 2009), whereas the probability of ureteral injury in laparoscopic operations increases by 0.2-6.0% (Cholkeri-Singh et al, 2007;Tanaka et al, 2008). This increased risk is due to the limitations of visual exposure, the lack of touch, and the use of an energy apparatus.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In open surgery, as the difficulties of operations increase, the probability of ureteral injury increases by 0-2.0% (Uccella et al, 2007;Chong et al, 2009), whereas the probability of ureteral injury in laparoscopic operations increases by 0.2-6.0% (Cholkeri-Singh et al, 2007;Tanaka et al, 2008). This increased risk is due to the limitations of visual exposure, the lack of touch, and the use of an energy apparatus.…”
Section: Discussionmentioning
confidence: 96%
“…Quinlan et al (2009) found that the use of a ureteral catheter could increase discrimination in complicated pelvic surgery, thus diminishing injury through negligence. Tanaka et al (2008) showed that preventively setting a ureteral catheter was beneficial for discerning the ureter, and could prevent ureteral injuries in laparoscopic hysterectomy; it could also spontaneously heal mild injuries of the ureter through prolonged intubation. In contrast, Kuno et al (1998) showed that indiscriminately applying a temporary ureteral catheter in gynecological surgery was not helpful for preventing ureteral injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Side effects like lower backache and hematuria occur frequently in most patients. 7 There is however no difference in incidence of ureteric injuries if prior stenting is done in all routine cases. Diagnosis of ureterovginal fistula is confirmed by a three swab test, IVP and if required cystoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…To prevent complications during the learning curve, perioperative recommendations should be formulated. Many of these recommendations have been reported in articles and text books [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25].…”
mentioning
confidence: 98%